KAJIAN FAKTOR YANG BERPENGARUH DALAM KENAIKAN PANGKAT/JABATAN PUSTAKAWAN - Endang Fatmawati (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2014)
Librarian is a certain functional positions. If the number of credits already completed and elements of performance appraisal or implementation work in DP3 at least good, so a librarian could be promoted every two years or up positions every year. In practice many factors that influence the promotion / librarian position. These factors can be categorized into internal factors and external factors. Competency of librarians into the resulting performance parameters of a librarian and can be assessed by the number of credits. In addition to the competence of the librarian is concerned, the party who was also influence in the career development librarians are: immediate supervisor, the employee, and the assessment team.